Development of a management model to address the impact of work-related stress on teachers’ mental well-being in South African primary schools - Tebogo E. Selebano; Arnel P. Huisamen; René Pellissier (SA Journal of Human Resource Management, 2025)
Orientation: Work-related stress has deleterious effects on mental health, resulting in disorders such as anxiety, depression and increased absenteeism.